Cross-Cultural Examination of University Education and Ego Integrity in Late Adulthood: Implications for Policy and Practice. Issue 6 (2nd November 2021) - Šolcová, Iva; Děchtěrenko, Filip; Poláčková Šolcová, Iva; Hofer, Jan; Busch, Holger; Au, Alma
ABSTRACT: Studies on education generally find that higher education has a positive impact on various aspects of life. Nevertheless, studies focused on elderly people and their psychosocial health and development seldom view higher education as an important factor. Our aim was to explore the relation between higher education and ego integrity, a measure based on Erikson's concept of psychological maturity in later life. We used four national samples of non-institutionalized elderly people from Cameroon (N = 238), China (N = 254), Czech Republic (N = 167), and Germany (N = 240). Relationships between ego integrity and several possible moderator variables were tested by multivariate regressions in each sample. Between-subject ANOVA was employed to test differences in ego integrity between university educated and non-university educated people. We found that ego integrity is affected by culture in interaction with gender and the level of education attained. University-educated people reported higher ego integrity than persons with lower education in three of four cultural samples, which suggests a relatively stable relationship between university education and ego integrity when controlling for gender, age, and working status. These findings highlight the importance of education in late adulthood. In terms of policies and practice, they underscore the importance of reduction of educational inequalities as well as desirability of improved access to higher education, expansion of opportunities for the achievement of complete education in later life, and facilitation and support of lifelong learning.